The interplay of children's rights and international refugee law: protection and best interests of the refugee and asylum-seeking child - Brittle, F. Ruth (2019)
There is broad acceptance of the interaction between international human rights law (IHRL) and international refugee law (IRL) and that the growing alignment between both areas of international law contributes to the development of IRL. Nevertheless, the child is often invisible or incorrectly assessed in a refugee status determination process. The United Nations Convention on the Rights of the Child (CRC) is recognised as an interpretative instrument to assess refugee children’s claims. This is evidenced in contexts including the interpretation of the definition of ‘refugee’ in the Refugee Convention, the determination of the ‘being persecuted’ criteria, the non-refoulement duty of the state and as a potential additional source of protection for children. The best interests principle in Article 3(1) CRC, which renders children’s best interests a primary consideration in all actions concerning them (including refugee and asylum-seeking children) has been used to balance a child’s interests against the interests of others in cases involving them. The principle has become a dominant feature in asylum cases where children are involved, with the child’s interests being balanced against those of the state. The growing alignment between IHRL (including children’s rights) and IRL reflects the fact that IRL is moving towards a rights-based approach to protection in the context of child asylum claims, but that the parameters of protection are interpreted too restrictively. This is due to a narrow interpretation of the best interests principle, resulting in the privileging of state interests over the refugee child’s protection and rights. My thesis argues that this state of affairs is problematic in terms of ensuring the protection and the rights of refugee children. It does so on the basis that the balancing exercise currently carried out by decision-makers ignores the obligation of the state under Article 3(2) CRC to protect and care for the child as is necessary for their well-being. The thesis argues that this obligation, which complements the best interests principle in Article 3(1) CRC, as well as the obligation to provide ‘appropriate protection and humanitarian assistance’ to refugee children under Article 22 CRC amounts to a right to protection for the refugee child in terms of the CRC. This right should be an integral part of the operationalisation of the best interests principle in decision-making about the refugee child.